MICROFINANCE INSTICase Study on Gakin Bank JemberTUTION AS AN ALTERNATIVEOF MSMEs DEVELOPMENT PROJECT - Putri, Nadia Azalia (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2015)
Abstract: Gakin Bank is a microfinance institution (MFI) aims to reduce the poverty rate in Jember. The limited employment opportunities had forced the poor people to build their own informal business. However, the difficulty in gaining the capital loan and the high level of interest rate offered by formal banks were the major obstacles for the poor to develop their business. Gakin Bank was built responding to such condition. This research aims to analyze performance and capacity building of Gakin Bank. The analytical methods used are descriptive analysis approach and SWOT analysis. The data used are primary data from the interviews and secondary data obtained from various sources. Results show that MFI has an important role as the micro financial institution in lending funds to the poor people and also for the empowerment of Micro, Small, and Medium Enterprises (MSMEs). Keywords: Gakin Bank, Microfinance Institutions, MSMEs, Development